How Does Irish Higher Education See Itself? - Hazelkorn, Ellen; Boland, Tom (International Higher Education, 2020)
A survey of senior leaders in Irish higher education shows considerable support for key national objectives for higher education, but issues of accountability, regulation, institutional governance, and management are all viewed negatively by respondents. The survey and this article were completed before the COVID-19 pandemic, which has presented a whole new set of issues for governments and institutional leaders. Yet all these issues remain relevant.